Implementasi Simpatika sebagai Media Sistem Informasi Kepegawaian di Madrasah Ibtidaiyah Swasta (MIS) Nurul Hidayah - Hendra Kurniawan; Ovi Ardilla; Lilis Juliyanty Marbun; Lathifatun Nisa Hutabarat; Syarah Nabila Pulungan (Lembag, 2025)
Digital transformation in the field of education not only focuses on learning processes but also includes institutional management, particularly in administrative staffing. The SIMPATIKA application, implemented in madrasahs under the Ministry of Religious Affairs, serves as a strategic step toward standardizing and improving the management of educator and staff data nationwide. This study employed a qualitative method and examined the implementation of SIMPATIKA at MIS Nurul Hidayah. The findings indicate that the use of SIMPATIKA has had a positive impact on staffing administration, making it more effective, transparent, and accountable. The system facilitates teacher data management, allowance submissions, and real-time attendance tracking. However, challenges such as limited internet connectivity, lack of training, and the need for additional features still need to be addressed through appropriate strategies.